A New Alchemical Poem Attributed to Khālid b. Yazīd (d. ca. 705). (3rd July 2017) - Saliba, George
Abstract : This paper deals primarily with the identification of an inaccurately catalogued alchemical poem attributed to the famous Umayyad prince Khālid b. Yazīd (d. 705), edited, translated, and commented upon here for the first time. The paper also addresses the authenticity of Khālid's interest in alchemy and connects that interest to the need of the early Islamic empire to develop its own gold coinage as a sign of political independence from Byzantine coinage that was up till then the currency of the lands occupied by early Muslims in the regions of modern-day Egypt and Syria. On the matter of the legendry character of Khālid which was apparently started by Ibn Khaldun and passed on after him to most nineteenth-century and early twentieth-century orientalists, the paper exposes here the inner contradictions in Ibn Khaldun's theorising on the matter, and his failure to understand why someone like the historical Prince Khālid would be interested in alchemy.